2021
DOI: 10.26719/emhj.20.126
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment: knowledge, attitudes and reporting behaviour of physicians in teaching hospitals, Egypt

Abstract: Background: Lack of diagnosis and reporting of child maltreatment are important problems worldwide. Aim: This study aimed to assess the knowledge, attitude and practice of physicians in Alexandria University teaching hospitals about the diagnosis and reporting of child maltreatment cases. Methods: A descriptive cross-sectional study was conducted at three hospitals. All physicians working regularly in emergency units were invited to complete a self-administered questionnaire. Data collected included sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
1
8
3
Order By: Relevance
“…It is important to teach this topic to medical students, as they are future physicians, and poor knowledge and awareness of CAN in medical students will increase the number of CAN cases going unnoticed [ 7 , 9 , 16 , 19 ]. In the literature, one study in Saudi Arabia comparing CAN awareness among medical interns and students in a local university in 2021 stated that knowledge of reporting systems in medical students was inadequate, and in another one, although medical students took formal training on CAN, many of them agreed on needing further training in this field [ 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to teach this topic to medical students, as they are future physicians, and poor knowledge and awareness of CAN in medical students will increase the number of CAN cases going unnoticed [ 7 , 9 , 16 , 19 ]. In the literature, one study in Saudi Arabia comparing CAN awareness among medical interns and students in a local university in 2021 stated that knowledge of reporting systems in medical students was inadequate, and in another one, although medical students took formal training on CAN, many of them agreed on needing further training in this field [ 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to emphasize that, in contrast to research done in the pre-pandemic period, medical students are more familiar with this topic, and that this knowledge is mostly tied to the year of the course to which they belong (15)(16)(17). Indeed, after evaluating the significant variables in the regression, only the covariate on course year remained statistically significant on awareness of child maltreatment.…”
Section: Discussionmentioning
confidence: 96%
“…However, it is important to emphasize that, in contrast to research done in the pre-pandemic period, medical students are more familiar with this topic, and that this knowledge is mostly tied to the year of the course to which they belong ( 15 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, without a system of mandated reporting, a society may be far less able to protect children because many cases of suspected abuse and neglect will not come to the attention of authorities [ 29 ]. In Egypt, the law does not mandate reporting of suspected abuse in children and health care professionals are not penalized if they do not report such cases [ 30 ]. Reporting, however, is mandated in many countries [ 5 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that dentists without training to manage suspected abuse were less likely to know how to report suspected abuse than those with training [ 35 ]. Also, prior studies including Egyptian physicians [ 30 ] and primary health care workers [ 36 ] similarly showed that health professionals needed training to be familiar with rules and supporting bodies so there seems to be a consensus that this training gap needs to be filled. Training that focuses on promoting positive attitudes towards reporting and increases awareness of existing laws, policies, and agencies in local context may lead to more reporting than training which aims exclusively at increasing the knowledge of the manifestations of abuse and how to identify abuse victims.…”
Section: Discussionmentioning
confidence: 99%